2015
DOI: 10.12659/msm.894146
|View full text |Cite
|
Sign up to set email alerts
|

Is Free Testosterone Concentration a Prognostic Factor of Survival in Chronic Renal Failure (CRF)?

Abstract: BackgroundLowered testosterone level in CRF patients is associated with elevated risk of death due to cardiovascular reasons, and is influenced by many factors, including acid-base balance disorders. Aims: evaluation of testosterone concentration (TT) and free testosterone concentration (fT) in pre-dialysis and dialysis patients; assessment of TT and fT relationships with biochemical parameters; evaluation of prognostic importance of TT and fT in predicting patient survival.Material/Methods4 groups of men: 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In the single Polish publication concerning the relationship between testosterone and prognosis in patients with CKD, Niemczyk et al implied that serum free testosterone concentration might be a better predictor of survival than age [ 17 ]. Likewise, in the presented study, FT, with a cut-off value of 54.6 pg/mL determined on the basis of the ROC curve, was the best prognostic parameter among all androgens in male hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the single Polish publication concerning the relationship between testosterone and prognosis in patients with CKD, Niemczyk et al implied that serum free testosterone concentration might be a better predictor of survival than age [ 17 ]. Likewise, in the presented study, FT, with a cut-off value of 54.6 pg/mL determined on the basis of the ROC curve, was the best prognostic parameter among all androgens in male hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hypogonadism is a group of clinical symptoms resulting from testosterone deficiency (low concentrations of total/free testosterone) explained by multifactorial causes [ 9 , 10 ]. Testosterone deficiency in men is associated not only with sexual dysfunction but also with an unfavorable cardiometabolic profile, both in the general population [ 11 , 12 , 13 ] and patients with chronic kidney disease [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone therapy in men with hypogonadism might produce lean muscle mass gain, increased muscle strength and size, as well as weight loss . Hence, testosterone levels were correlated and associated with skeletal muscle mass and low testosterone concentrations might predict long‐term survival in those with CKD or dialysis …”
Section: Introductionmentioning
confidence: 99%
“…18,19 Hence, testosterone levels were correlated and associated with skeletal muscle mass and low testosterone concentrations might predict long-term survival in those with CKD or dialysis. 20,21 The aim of this study was to evaluate prognostic importance of serum testosterone in elderly men with hemodialysis and whether low testosterone levels were superior to low skeletal muscle mass in predicting mortality or not. As testosterone level predicted mortality in male HD patients was largely dependent on age, 14 we restricted our study population to elderly men to minimize the confounding effect of age and analyzed multiple risk factors and comorbid conditions at start of dialysis, including skeletal muscle mass index (SMMI), serum testosterone, BMI, and well-known risk factors for mortality after dialysis in a regional hospital.…”
mentioning
confidence: 99%
“…Evidence has suggested a correlation between CRF and low serum levels of 1, 25-dihydroxyvitamin D3 (calcitriol or 1, 25[OH]2D3) as well as the reactive metabolite of vitamin D3 due to a reduction in renal 1α-hydroxylase (CYP27B1) [3]. CRF shares a strong association with older age along with an age-induced decline in renal functions resulting from conditions including vascular disease, hypertension, hepatitis C (HCV) infection, and diabetes mellitus [4][5][6]. An investigation into mesenchymal stem cells as a potential therapy for kidney injuries revealed that when endstage kidney disease is reached, renal transplantation is regarded as the optimal therapeutic approach, but there are several limitations, including a lack of organ donors and immune reactions observed within the five-year posttransplantation period, and these limitations vary across different age groups [7,8].…”
Section: Introductionmentioning
confidence: 99%